2022
DOI: 10.1002/we.2769
|View full text |Cite
|
Sign up to set email alerts
|

Including the power regulation strategy in aerodynamic optimization of wind turbines for increased design freedom

Abstract: In wind turbine optimization, the standard power regulation strategy follows a constrained trajectory based on the maximum power coefficient. It can be updated automatically during the optimization process by solving a nested maximization problem at each iteration. We argue that this model does not take advantage of the load alleviation potential of the regulation strategy and additionally requires significant computational effort. An alternative approach is proposed, where the rotational speed and pitch angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The maintenance costs and the total lifetime energy output are dependent on how the system operates and, consequently, depend on the environment and how it is controlled [21,22]. Recent studies have shown that advanced control strategies for offshore wind applications can increase the power extracted from the turbine and minimize the levelized cost [23,24]. Most conventional LCOE estimates have not incorporated detailed dynamic assessments nor the impact of novel control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance costs and the total lifetime energy output are dependent on how the system operates and, consequently, depend on the environment and how it is controlled [21,22]. Recent studies have shown that advanced control strategies for offshore wind applications can increase the power extracted from the turbine and minimize the levelized cost [23,24]. Most conventional LCOE estimates have not incorporated detailed dynamic assessments nor the impact of novel control strategies.…”
Section: Introductionmentioning
confidence: 99%